Respuesta inicial de una plantación de dos procedencias de Juglans neotropica Diels a la fertilización aplicada en tres estratos en la “Hacienda La Florencia” del Cantón y la Provincia de Loja - Reátegui Ramón, César Gustavo (2022)
The establishment of forest plantations with native species presents high mortality values in the initial development. Thus, the efforts and strategies to solve this problem have been oriented from the origin of the plant material, care at the nursery level, and silvicultural practices, to solve this condition and ensure the growth of seedlings, either for commercial, restoration, enrichment, or conservation. In this context, open-pollinated seeds from two natural sources were collected, and their seedlings were established in September 2020 at "Hacienda La Florencia" in Loja Canton. This process evaluated the survival and initial adaptability of a plantation of two provenances of Juglans neotropica Diels established in three strata and compared the growth of the dasometric variables to the fertilization with NPK and Urea in different concentrations. Twelve months after the plantation was established, the survival variables, total height, and diameter at the base were evaluated for each stratum and provenance. The plantation presented a 90,92 % survival. The secondary forest stratum recorded 100 % survival and the highest average height growth. The riparian zone stratum obtained 90 %, while the paddock stratum, with a survival of 82,78 %, obtained the highest average growth in diameter with the seedlings of both origins. The first year after being fertilized, the seedlings from El Tundo presented higher growth averages in diameter and height in the three strata compared to the seedlings from the La Victoria parish. However, the dasometric variables' growth differences under the treatments' application were insignificant. Keywords: Strata, Juglans neotropical Diels, fertilization, growth, provenances, dasometric variables.